Factors Affecting Income Smoothing in Manufacturing Companies Listed on the IDX (2016-2019 Period): Faktor yang Mempengaruhi Perataan Laba (Income Smoothing) pada Perusahaan Manufaktur yang Terdaftar di BEI (Periode 2016-2019) - Arifcha Nelly; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the Factors Affecting Income Smoothing (Study on Food and Beverage Companies Listed on the Indonesia Stock Exchange 2016-2019). The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 13 Food and Beverages Listed on the IDX for the 2016-2019 period. The data used is secondary data. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that company size has an effect on income smoothing in food and beverage companies listed on the Indonesia stock exchange in 2016-2019. Profitability Affects Income Smoothing in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2016-2019. Debt Ratio Affects Income Smoothing in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2016-2019. Taxes have an effect on Income Smoothing in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2016-2019. Highlights: The study examines income smoothing in food and beverage companies listed on the Indonesia Stock Exchange from 2016 to 2019 using secondary data. Company size, profitability, debt ratio, and taxes are identified as factors affecting income smoothing in the studied companies. Multiple Linear Regression is employed as the data analysis method to analyze the relationships between the variables and income smoothing. Keywords: Income smoothing, Food and beverage companies, Indonesia Stock Exchange, Company size, Profitability